Gambaran Persepsi Mutu Pelayanan Kesehatan pada Pasien Pengguna JKN di Puskesmas Karangmoncol - Setiawati, Ayu; Arumsari, Wahyuni; Rahayu, Sri (Indonesian Journal of Health Community, 2023)
Health services are an integrated and sustainable effort to maintain and improve a high level of health. Protection of public health is realized through quality implementation in accordance with the demands of Law of the Republic of Indonesia Number 36 of 2009. Community Health Centers which have the largest service locations in Karangmoncol District should provide good mutual services. The aim of this research is to see a picture of mutual service for patients using JKN at the Karangmoncol Health Center in 2023. This type of research is quantitative descriptive and was carried out in May - July 2023. Sampling was taken using the purpouse sampling technique, resulting in 100 respondents. The data analysis used was univariate using frequency. From the research results, it was found that the dimensions of health service quality were reliability of 80%, responsiveness of 80%, assurance of 83%, empathy of 75%, tangible of 86 %. So it can be concluded that the majority of respondents in this study had a good perception of the quality of health services at the Karangmoncol Community Health Center.